Asymmetric competition between sympatric endangered primates affects their population recovery. (August 2020) - Chen, Yuan; Ma, Chi; Yang, Li; Guan, Zhenhua; Jiang, Xuelong; Fan, Pengfei
Abstract: Species interactions including predation, competition, and parasitism, matter to species conservation. Sympatric species can have a profound influence on the population recovery of endangered species through a number of ecological processes, but particularly feeding competition. We investigated ranging (spatial pattern) and feeding (trophic overlap) behavior of sympatric critically endangered western black crested gibbons ( Nomascus concolor ) and endangered Indochinese gray langurs ( Trachypithecus crepusculus ). Our 1-year study of one group of each species found potential for asymmetric feeding competition between langurs and gibbons on Mt. Wuliang, China, in that: (1) the home range (2 km 2 ) of the gibbon group was nearly entirely within the home range of the langur group (4.2 km 2 ); (2) langurs had a greater niche breadth than gibbons, and their trophic overlap was 0.23; (3) 14 out of 26 primary food items comprising 56.7% of gibbon annual diet were consumed by langurs; and (4) langurs routinely consumed unripe fruits before they ripened sufficiently for gibbons to eat. Differences in group size, feeding habits, and reproductive rate could increase the effects of asymmetric dietary in potential competition, which appears to limit population recovery of gibbons. Rapid recovery of one species may cause unintended conservation consequences through complex interspecific interaction. Thus, it is important that conservation strategies take species interactions into account when designing conservation interventions. To ensure the ongoing survival of gibbons it may be necessary to manage langur populations.